Keanekaragaman Kupu-Kupu di Hutan Kota Munjul Sebagai Indikator Kualitas Lingkungan - Lin Nuriah Ginoga; Siva Devi Azahra; Siti Badriyah Rushayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to identify the diversity of butterfly species in Hutan Kota Munjul. The method used was a 500 m line transect combined with trapping and exploratory techniques. Butterfly sampling was conducted using insect nets during sunny weather between 09:00–12:00 and 14:00–16:00 WIB. The data collected included species, number of individuals, encounter points, host vegetation, temperature, humidity, and water sources. Data were analyzed qualitatively and quantitatively to determine encounter points, diversity index, richness index, and evenness index. The results showed that 25 butterfly species from five families were identified, namely Papilionidae, Nymphalidae, Pieridae, Hesperiidae, and Lycaenidae. In conclusion, Hutan Kota Munjul has a relatively good level of butterfly diversity supported by suitable habitat conditions, indicating its potential as a green open space that supports biodiversity. Keywords: Hutan Kota Munjul, Biodiversity, Butterflies